P-260 Developing an on-line toolkit to support end of life care. Issue Volume 8: Issue (2018)Supplement 2 (November 2018) - Shreeve, Philippa; England, Ruth
Abstract : Background: When the LCP was removed, a range of materials and guidance required review; furthermore, revised practice needed a platform in order to be shared. We recognised that a new approach might be supported by a novel on-line resource. Methods: A suite of tools that could be used by different providers across Derbyshire at different stages in a patient's end of life journey were collected together. Initially, these documents were held on a webpage hosted by a local community healthcare provider. An accompanying webpage contained details of upcoming educational events and contacts. In the first six months these pages had approximately 6500 hits, with each visit lasting on average 2.5 min. However, feedback stated the pages were not easily accessible to all staff and were clumsy to use. Funding was obtained to build a more 'user friendly' resource. An improved platform was launched in October 2015. Results: In the period 1 October 2016 to 30 September 2017, 9862 sessions were conducted on our website by 5842 users. The average number of pages viewed per session was 3.6 with an average session duration being 3'34'. More than 50% of users in this period were new to the website and our low bounce rate suggests that people who come to us find what they are looking for. The most popular resource is symptom management guidance. Most activity still comes from desktop computers but users do access the website via mobile devices. It is now possible to create an individualised learning portfolio using the toolkit. This can be linked to existing accredited resources (eELCA) as well as signposting to local face-to-face events. Conclusions: This novel website is a well-used platform for a suite of resources, as well as a means of educational support for those engaging in end of life care.